IDENTIFIKASI JENIS CEDERA OLAHRAGA YANG PALING SERING DIALAMI OLEH PEMAIN BULU TANGKIS - Nimrot Manalu; Abdul Aziz Nasution; Royhan Taher Hasibuan; Rico Sorimuda; Imam Hidayat; Andes Martua Harahap (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the types of sports injuries most frequently experienced by badminton players, their locations, and the factors that can trigger them. The method used was descriptive analysis through a literature review of scientific sources published in the last five years. The analysis showed that 70% of athletes had experienced an injury. In the upper body, the elbow was the most common injury site (30%), due to errors in hitting technique. Meanwhile, in the lower body, the ankle was the most frequently affected (40%) due to careless footwork. The most common type of injury was muscle spasm (45%). This is caused by improper technique, inadequate warm-up, and suboptimal physical condition. Addressing problems incorrectly can risk serious physical injury and even psychological trauma. Therefore, athletes are advised to maximize their warm-up, and coaches need to focus more on improving basic technique.